Water and Power Reserve Capacity of Health Facilities in the Greek Islands. Issue 2 (13th February 2014) - Alexakis, Lykourgos-Christos G.; Codreanu, Tudor A.; Stratton, Samuel J.
Abstract Introduction Geographically isolated islands are vulnerable during natural or technological disasters. During disasters, island health facilities should be able to secure power and water in order to continue operations. Objective This study sought to determine the existence of Greek island health facility backup systems for water and power. When such systems existed, reserve capacity was quantified and compared to the Pan American Health Organization (PAHO) Hospital Safety Index standards. Methods A standardized, self-administered questionnaire was sent to major health care facilities belonging to the national health system in all Greek islands. The biggest facility available in each island was included (hospital, health center, or health post). For Crete and Euboea, all hospitals were included. Results Fifty-four of 85 facilities queried (27 hospitals, 17 health centers and 41 health posts) responded, for a response rate of 64%. Responding to the survey were 16 hospitals, 12 health centers and 26 health posts. In 70% of responding facilities (all 16 hospitals, 10 health centers, and 12 health posts) a backup water tank was available, while 72% (all 16 hospitals, 11 health centers, and 12 health posts) had a backup power supply system. Twenty-seven facilities provided data on water reserve, with 15 (56%) reporting a reserve for three or more days. Twenty facilities provided data on fuel stock and power consumption; six (30%) had energy reserves for more than 72 hours, and eight (40%) had reserves for 24-72 hours. Conclusions Greek state-supported island health facilities responding to the questionnaire had water and power reserves for use in an emergency. Health centers and health posts were less prepared than hospitals. Of the responding health facilities, half had a water backup system and approximately one-third had power backup systems with reserves that would last for at least 72 hours. <mixed-citation id="ref" publication-type="journal"> <string-name> <given-names>LC</given-names> <x content-type="archive" xml:space="preserve"> </x> <surname>Alexakis</surname> </string-name>, <string-name><given-names>TA</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Codreanu</surname></string-name>, <string-name><given-names>SJ</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Stratton</surname></string-name>. Water and power reserve capacity of health facilities in the Greek islands . <source>Prehosp Disaster Med</source>. <year>2014</year>;<volume>29</volume>(<issue>1</issue>):<fpage>1</fpage>-<lpage>5</lpage></mixed-citation>.